Fertility studies of semen preserved in coconut milk extender - George P K (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 1978)
The object of the study was to assess the fertility of semen extended in CME at various periods of storage In comparison with semen extended in EYC. Semen samples collected from three breeding bulls maintained at the Artificial Insemination Centre, Mannuthy were diluted with CMSE and EYC using split sample technique and stored at room temperature and at 50C respectively. Both the samples were preserved upto 96 hours and utilised for the study, A total number of 1112 animals ware utilised for the fertility evaluation. Alternate animals were inseminated with semen extended in CME or EYC. Conception rates were estimated on the basis of rectal examination. Data from the field comprising of 18,245 first inseminations with CME from 55 artificial insemination centres in Kottayam district were also incorporated in the study. The overall conception rate did not vary significantly between CME and EYC extended semen. The conception rate in cows was significantly higher than in heifers both in CME and EYC. Within the same period of storage, conception rate between CME and EYC was not found significant. In EYC, a significant fall in the conception rate was observed after 48 hours of storage but in CME this was noticed only after 72 hours of storage. The variation in the fertility rate between the bulls was not found to be significant. Higher conception rate was observed in the experimental animals than in the field. Significant fall in the conception rate was observed in the field after 48 hours of storage. Seasonal variation in the conception rate was observed, with higher percentage conception in rainy season (June to October) and lower in winter (November to January). Highly significant difference in the fertility of bulls used in the field was also observed. In conclusion, it may be stated that semen preserved in CME can be used up to 72 hours of storage time without substantial reduction in the fertility.